Assessment of the non-communicable diseases kit for humanitarian emergencies in Yemen and Libya. (7th July 2022) - Kiapi, Lilian; Alani, Ahmad Hecham; Ahmed, Iman; Lyons, Gemma; McLain, Grace; Miller, Laura; Darji, Bhavika; Waweru, Isaac; Aragno, Mauricio; Kisarach, Kelly; Zeleke, Mekuanint; Nagi, Nabeel; et al.
Abstract : Emergency health kits are a vital way of providing essential medicines and supplies to health clinics during humanitarian crises. The WHO non-communicable diseases (NDCs) kit was developed 5 years ago, recognising the increasing challenge of providing continuity of care and secondary prevention of NCDs and exacerbations, in such settings. Monitoring and evaluation of emergency health kits is an important process to ensure the contents are fit for purpose and to assess usability and utility. However, there are also challenges and limitations in collecting the relevant data to do so. This Practice paper provides a summary of the key methodologies, findings and limitations of NCD kit assessments conducted in Libya and Yemen. Methodologies included a combination of semistructured interviews, surveys with healthcare workers, NCD knowledge tests and quantifying the remaining contents. The kit was able to support the vital delivery of NCD patient care in some complex humanitarian settings and was appreciated by health facilities. However, there were also some challenges affecting kit use. Some kit contents were found to be in greater or lesser quantities than required, and medicine brands and country of origin affected acceptability. Supply chains were affected by the humanitarian situations, with some kits being held up for months prior to arrival. Furthermore, healthcare staff had received limited NCD training and were unable to dispense certain medicines, such as psychotropics, at the primary care level. Further granularity of kit modules, predeployment facility assessments, increased NCD training opportunities and a monitoring system could improve the utility of the kits.